Matrine Inhibits Breast Cancer Cell Proliferation and Epithelial-Mesenchymal Transition Through Regulating the LINC01116/miR-9-5p/ITGB1 Axis - Lili Ren; Ziru Fang; Jiaojiao Xu; Xiaoxiao Wu; Yongjun Zhang; Hu Cai; Zhicun Han (Balkan Medical Journal)
Background: Breast cancer (BC) is the most prevalent solid cancer affecting women’s health globally. Matrine (MAT), a traditional Chinese herb, has exhibited antitumor effects against BC. However, its mechanism of action, particularly whether it involves the control of cell proliferation and epithelial-mesenchymal transition (EMT), remains unknown. Aims: To explore MAT’s role in BC and its regulatory mechanisms, as well as to identify targets for the development of novel medicines and improvement of BC treatment modalities. Study Design: Experimental study. Methods: The UALCAN and Lnc2Cancer 3.0 databases were used to predict the expression of LINC01116 in BC. The BC cells (MDA-MB-231 and MCF-7) were treated with various concentrations of MAT, and the optimal dose and timing of MAT action were determined using CCK-8 and quantitative real-time polymerase chain reaction assays. Functional assays such as CCK-8, EdU, Transwell, Western blot, and flow cytometry assays were performed on the BC cells, and the impacts of LINC01116, miR-9-5p, and ITGB1 expression levels on MAT’s mechanism of action were assessed. The association between LINC01116, miR-9-5p, and ITGB1 was evaluated using dual luciferase and RNA immunoprecipitation assays. Furthermore, the size and weight of the subcutaneous tumors in mice model were assessed. The effect of LINC01116 overexpression on the in vivo action of MAT and histopathological staining (TUNEL immunofluorescence, hematoxylin & eosin staining, immunohistochemistry staining for Ki67 and Bax) were also assessed. Results: The optimal dose and duration of MAT administration were 8 µm and 24 h, respectively. MAT effectively inhibited BC cell proliferation, EMT progression, and biological functions, while promoting BC cell apoptosis. The animal model experiments also demonstrated that MAT inhibited BC tumor growth in vivo. Furthermore, MAT inhibited LINC01116, which acted as a sponge for miR-9-5p, increasing the ITGB1 level. Conclusion: MAT suppresses BC cell and EMT proliferation via the LINC01116/miR-9-5p/ITGB1 pathway. Thus, MAT may be a promising target for adjuvant anti-BC therapy.